2007
DOI: 10.1080/02508281.2007.11081539
|View full text |Cite
|
Sign up to set email alerts
|

Cultural Landscape Interpretation: The Case of the Sorry Rock Story at Uluru-Kata Tjuta National Park

Abstract: At Ulu_ru-Kata Tju!_a National Park complex negotiations take place in presenting and interpreting the cultural landscape for tourists. The joint management philosophy of the Park means that interpretive outcomes are the result of regular dialogue between A!!angu, the traditional owners of the Park, and Park management. This paper focuses on research associated with the management and presentation of an emerging story in the Ulu_ru landscape, known as the 'sorry rocks'. Each year several hundred people return … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Parks and Indigenous peoples are deeply intertwined the world over, from issues of sacred site management at Uluru-Kata Tjuta, to forced evictions on the Maasai Mara, to the development of cooperative management regimes on Haida Gwaii (Disko and Tugendhat 2014;Jones, Rigg, and Lee 2010). Scholars have developed a robust catalogue of literature about park-Indigenous interactions, drawing on fields as diverse as history (Spence 1999), heritage interpretation (Foxlee 2007), anthropology (Daehnke 2017), Indigenous studies (Nadasdy 1999), political science (White 2020), and park management (Stevens 2014). The scholarship has drawn clear connections between protected area management and processes of settler colonialism (Brockington and Igoe 2006;Colchester 2014;Kelly 2011;Sandlos 2007), both of which are concerned with extending the state's authority over land (Coulthard 2014;Mackey 2016;Simpson 2011).…”
Section: Indigenous Peoples and Protected Areasmentioning
confidence: 99%
“…Parks and Indigenous peoples are deeply intertwined the world over, from issues of sacred site management at Uluru-Kata Tjuta, to forced evictions on the Maasai Mara, to the development of cooperative management regimes on Haida Gwaii (Disko and Tugendhat 2014;Jones, Rigg, and Lee 2010). Scholars have developed a robust catalogue of literature about park-Indigenous interactions, drawing on fields as diverse as history (Spence 1999), heritage interpretation (Foxlee 2007), anthropology (Daehnke 2017), Indigenous studies (Nadasdy 1999), political science (White 2020), and park management (Stevens 2014). The scholarship has drawn clear connections between protected area management and processes of settler colonialism (Brockington and Igoe 2006;Colchester 2014;Kelly 2011;Sandlos 2007), both of which are concerned with extending the state's authority over land (Coulthard 2014;Mackey 2016;Simpson 2011).…”
Section: Indigenous Peoples and Protected Areasmentioning
confidence: 99%
“…These connections are important for the relationship with visitors (see 5.2.2.6), and also to facilitate an understanding of Māori cultural heritage by making the interpretation more relevant and meaningful. Visitors bring their own perspectives, values and contexts for understanding and gaining meaning, as reiterated in the literature (Amoamo & Thompson, 2010;Foxlee, 2007;Hooper-Greenhill, 2000;McIntosh & Johnson, 2004;Moscardo, 1996). Schorch"s (2010) study demonstrates how visitors use their own reference frame to gain an understanding of Māori culture.…”
Section: Facilitating Connections and Meaning Makingmentioning
confidence: 99%
“…As discussed by Foxlee (2007), the multiple sources of information, multiple voices and perspectives may have conflicting meanings. The shift in cultural representation and the incorporation of indigenous perspectives has been discussed in the literature on indigenous tourism and Māori tourism (Amoamo, 2007;Amoamo & Thompson, 2010;Batten, 2005;Bunten, 2010;Carr, A., 2004;Foxlee, 2007), and in the context of museums (Hooper-Greenhill, 2000McCarthy, 2011). This shift towards the incorporation of indigenous perspectives implies the inclusion of tribal perspectives.…”
Section: Narrative and Voicementioning
confidence: 99%
“…This is reiterated in Foxlee"s (2007) study of the interpretation of Aboriginal culture at Uluru which identified multiple and potentially conflicting meanings arising when visitors create their own meanings of place. Furthermore, the question of authorship of the narrative and the purposeful inclusion and exclusion of stories and perspectives, as well as the integration of indigenous knowledge systems into the interpretation practice is examined (Foxlee, 2007).…”
Section: Interpretation Of Indigenous Cultural Heritagementioning
confidence: 99%